Tephra layers along the southern Tyrrhenian coast of Italy: links to the X-5 and X-6 using volcanic glass geochemistry - Donato, P; Albert, P; Crocitti, M; De Rosa, R; Menzies, M (Elsevier, 2016)
We present the geochemistry of glass fragments from three visible tephra layers outcropping in Southern Italy. Two tephra deposits (LeS1 and LeS2), outcropping in the Palinuro area (Cilento, Southern Italy), correspond stratigraphically to the CIL1 and CIL2 tephra units (Giaccio et al., 2012), respectively; in turn these are correlated with the X-5 (ca. 105 ka) and X-6 (ca. 108 ka) marine tephra markers on the basis of their major element glass compositions. In order to reinforce these tephra correlations we examine both their major and trace element glass compositions. LeS1 compositions were compared with other correlatives of the X-5 tephra layer (POP3 [Sulmona basin], TM-25 [Lago Grande di Monticchio (LGdM)], CIL1 [Palinuro]) from the central Mediterranean. Our data validate a correlation of the Palinuro tephra layer, LeS1, to the X-5 correlatives. The Palinuro tephra deposit, LeS2, has glass compositions which correspond precisely with correlatives of the X-6 marker tephra (CIL2 [Palinuro], TM-27 [LGdM], I-9 [Ionian Sea] and PRAD 2812 [PRAD1-2, Adriatic Sea]). A tephra in the Valle del Crati (Calabria) appears to overlap in composition with the LeS2 tephra, indicating a probable correlation with the X-6 marker. These new data provide a detailed geochemical characterisation of two widespread marker horizons and are crucial for establishing precise correlations of sedimentary archives across the central Mediterranean region.